PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERPENDEKATAN JELAJAH ALAM SEKITAR (JAS) TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS VII SMP ISLAM JAILOLO - Amina H. Partjuma; Chumidach Roini; Arini Zohratun Nashicah (JURNAL BIOEDUKASI, 2022)
Education has an important role for humans, because with education humans can develop abilities and shape dignified character and national civilization in order to educate the nation's life to develop the potential of students to become human beings who are faithful, knowledgeable, and creative. The purpose of this study was to determine the effect of the Project Based Learning (PjBL) learning model with the Natural Exploration (JAS) approach on the cognitive learning outcomes of class VII students of SMP Islam Jailolo. This research is quasi-experimental research (Quasy Experiment). The population of this study consisted of two classes, namely class VII-A and class VII-B, which consisted of 55 students. The research sample is a total sample or full sample. Class VII-A as the experimental class was taught using the PjBL model with the JAS approach, while VII-B was the control class which was taught using the PjBL model. The instrument used to measure cognitive learning outcomes is a written test. The results of the data analysis used the SPSS-assisted normality and homogeneity tests, and the data were normally distributed and homogeneous, while the hypothesis test used the ANACOVA test and the result was that there was an influence of the PjBL learning model with the JAS approach on cognitive learning outcomes of class VII students of SMP Islam Jailolo at a significance level of 0 ,05.